Compressive Strength and Microstructure Properties of Alkali-Activated Systems with Blast Furnace Slag, Desulfurization Slag, and Gypsum - Bong-Suk Cho; Kyung-Mo Koo; Se-Jin Choi (Advances in Civil Engineering)
This study investigates the effect of desulfurization slag (DS) and gypsum (G) on the compressive strength and microstructure properties of blast furnace slag-(BFS-) based alkali-activated systems. DS is produced in a Kambara reactor process of molten iron produced in a steel production process. DS contains CaO, SiO2, Fe2O3, and SO3 and is composed of Ca(OH)2 and 2CaO·SiO2 as main compounds. In this investigation, the weight of BFS was replaced by DS at 5, 10, 15, 20, 25, and 30%. In addition, G was also applied at 9, 12, and 15% by weight of BFS to improve the compressive strength of the alkali-activated system with BFS and DS. According to this investigation, the compressive strength of the alkali-activated mixes with BFS and DS ranged from 14.9 MPa (B95D5) to 19.8 MPa (B90D10) after 91 days. However, the 28 days compressive strength of the alkali-activated mixes with BFS, DS, and G reached 39.1 MPa, 45.2 MPa, and 48.4 MPa, respectively, which were approximately 78.8 to 97.5% of that of O100 mix (49.6 MPa). The main hydrates of the BFS-DS (B80D20) binder sample were Ca(OH)2, CaCO3, and low-crystalline calcium silicate hydrates, while the main hydration product of BFS-DS-G (B75D10G15) binder was found as ettringite. The use of BFS-DS-G binders would result in the value-added utilization of steel slag and provide an environmentally friendly construction material, and contribute to a reduction of CO2 in the cement industry.